ملاءمة طريقة الحوار السقراطي في تنمية مهارة الكلام لدى طلاب الصف السابع بمدرسة الأزهر المتوسطة الإسلامية - مِنْجَانْتِي كَرْسِيكْ: The Relevance of the Socratic Dialogue Method in Developing Mahārah Kalām for Seventh Grade at MTs Al Azhar Menganti Gresik - Muhammad Imam Nawawi; Kamal Yusuf (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
Teaching Arabic at the junior secondary level faces several serious challenges, most notably the limited participation of students in oral communication and the dominance of lecture-based instructional approaches. This study aims to analyze the suitability of the Socratic dialogue method in developing speaking skills among seventh-grade students at Al-Azhar Islamic Junior High School, Menganti Gresik. This research employed a descriptive qualitative design. The participants consisted of seventh-grade students enrolled in Arabic language classes at the aforementioned school. Data were collected through classroom observations, semi-structured interviews with teachers and students, questionnaires, and an analysis of instructional documents and assessment reports. The data were analyzed using Miles and Huberman’s model through the stages of data collection, reduction, categorization into thematic units, and verification of credibility through both source triangulation and method triangulation. The findings indicate that the implementation of the Socratic dialogue method enhances students’ active participation in oral interaction, strengthens their ability to formulate reflective questions and responses in Arabic, and promotes the development of critical thinking skills. However, several challenges were identified, including limited instructional time, unequal student participation, and increased cognitive load for some learners. The study suggests that integrating the Socratic dialogue method with task-based language teaching (TBLT), along with continuous teacher training, can improve its effectiveness in developing speaking skills in Arabic language classrooms.